Pulsed Radiofrequency on Sphenopalatine Ganglion as the Interventional Pain Management in Cluster Headache Secondary to Sphenoid Meningioma - Rahmasena, Naomi; Koeshardiandi, Mirza; Mudianto, Fajar Tri (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Cluster headache is one of the neurovascular headaches characterized by severe recurrent unilateral pain distributed around the orbit and accompanied by autonomic symptoms such as lacrimation, conjunctival injection nasal congestion or rhinorrhea, edema of the eyelid, sweating, and miosis. The attack usually lasts for 15 to 180 minutes. The possible mechanism of cluster headache is through the trigeminal-autonomic reflex. Management of the cluster headache is divided into pharmacological therapy including abortive and prophylaxis, as well as interventional pain management like deep brain stimulation, occipital nerve stimulation, and radiofrequency of the sphenopalatine ganglion. Objective: This report aims to demonstrate the effectivity of pulsed radiofrequency sphenopalatine ganglion on cluster headaches secondary to meningioma. Case Report: A 47-year-old female consulted the pain clinic with a chief complaint of profound facial pain for a year. The patient also reported autonomic symptoms such as rhinorrhea and lacrimation. The patient was diagnosed with meningioma and already treated with conventional therapy such as gabapentine, carbamazepine, omeprazole, and mecobalamin. Due to the location of meningioma which causes the tumor inoperable. The patient complained of constant and worsening pain, therefore pulsed radiofrequency on sphenopalatine ganglion was chosen to treat the patient. The patient reported relief of pain ever since. Discussion: Among the consequences and benefits, pulsed radiofrequency is the choice of interventional pain management. Possibly the pain from the compression of the greater palatine nerve, intervention on the sphenopalatine will cause relief of the pain. Pulsed radiofrequency on sphenopalatine ganglion was reported successful in alleviating the pain of the patient. Conclusion: Pulsed radiofrequency of the sphenopalatine ganglion successfully alleviates the pain of the cluster headache due to meningioma. However, further study with a bigger population is recommended to see the efficacy of interventional pain management objectively.